Fostering Economic Self-Reliance via Asset-Based Community Development (ABCD) in Entrepreneurial Practices - Asni; Lailatul Fitriani; Safitri; Syarif Hidayatullah; Nurfauziah Mansur; Moh. Anwar Zainuddin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2024)
Community economic empowerment through entrepreneurship is essential for achieving inclusive and sustainable development. Despite this, many communities continue to struggle with leveraging local resources effectively and remain reliant on external support. This community service initiative adopts the Asset-Based Community Development (ABCD) approach to enhance entrepreneurial capacities by harnessing local assets. The program involves several key stages: local asset identification, participatory planning, capacity-building workshops, business mentoring, and ongoing monitoring and evaluation. Data were collected through observations, structured interviews, and surveys to assess changes in knowledge, skills, and economic outcomes. Findings indicate substantial improvements in participants' entrepreneurial competencies, strengthened social networks, and increased business resilience, leading to reduced dependence on external aid. The ABCD approach demonstrates strong potential for mobilizing endogenous resources as a foundation for self-reliant and sustainable community economic development. This initiative offers a replicable model for supporting agribusiness development and holistic community empowerment.